Role of Cu-Mfi zeolite catalyst on direct conversion of methane ethane to gasoline - Norzita Ngadi,; Nor Aishah Saidina Arnin,; Didik Prasetyoko, (2005)
HZS'M-5 (Si/Al = 30), silicalite and Cu-MFI with different copper concentrations were synthesized by direct synthesis method. The catalyst samples were characterized using X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR) and Temperature Programmed Desorption of Ammonia (TPD-NH3) techniques. The catalytic performance of the samples was evaluated in a continuous micro packed-bed reactol: The reaction was performed at reaction temperature 800°C under atmospheric pressure. The effects of Cu content on methane conversion and products selectivity were investigated. Characterization results revealed that the samples were MFI-zeolite catalysts and the copper species most probably occluded in the defect sites of the zeolite. Modification of zeolite with copper resulted in the en-hancement of methane conversion up to 15 %. The experimental results using Cu(O.I)-MFI demonstrated a high selectivity to gasoline, which is 29.7%